Regional social capital and moral hazard in crowdfunding - Lin, Tse-Chun; Pursiainen, Vesa (Journal of Business Venturing, 2022)
We contribute to institutional and social capital theory by developing a theoretical framework that suggests that informal and formal institutions are important in mitigating moral hazard in reward-based crowdfunding. We analyze a large sample of Kickstarter campaigns to test these predictions. We find a strong positive relationship between entrepreneurs' home-county social capital and their crowdfunding performance. A rule change that strengthens entrepreneurs' obligation to provide backers with the promised rewards is associated with a reduction in the effect of social capital, suggesting that formal institutions can substitute for informal ones and provides causal evidence of the effect of social capital.